(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical and paraclinical characteristics of gallstone disease and to evaluate the outcomes of laparoscopic cholecystectomy in patients aged over 74 years. Materials and Methods: This was a cross-sectional descriptive study conducted on 35 patients aged over 74 years with acute cholecystitis due to gallstones, who underwent laparoscopic cholecystectomy at Viet Tiep Friendship Hospital from January 2024 to March 2026. Results: Among the 35 patients, there were 22 females and 13 males, with a female-to-male ratio of 1.69:1. The age group 75–89 accounted for 97.1%. No patients had a history of previous abdominal surgery. Hypertension was present in 42.9% of cases. Patients classified as ASA II accounted for 54.3%. Gallstones located in the gallbladder lumen were found in 88.6% of patients, while 11.4% had stones in the gallbladder neck. The main surgical approach was the retrograde (fundus-first) technique (91.4%). Intraoperative bleeding occurred in 2.9% of cases. Conversion to open surgery was required in 2.9%. Early postoperative complications occurred in 5.7%, including bleeding and surgical site infection. The mean hospital stay was 7.1 days. Early postoperative outcomes were good in 94.3% and fair in 5.7%. Conclusion: Laparoscopic cholecystectomy in patients over 74 years old is safe and does not increase surgical risks, despite the presence of multiple comorbidities.